Sociability dan Place Attachment Sebagai Faktor Livability Ruang Publik : (Kasus: Kawasan Permukiman Pecinan Pasar Lama Tangerang) - Alfiani Nur Lailika; Nurhikmah Budi Hartanti (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2024)
Providing access to safe and inclusive public spaces is the target of the UN's Sustainable Development Goals (SDGs). There are challenges to achieving this goal because of the high density in many areas in Indonesia, which occurs in the Pasar Lama area of Tangerang, causing limited public open space. Nevertheless, residents of the Pasar Lama area still actively use the available spaces between buildings, which may have different standards from the literature, as places for social activities. Thus, this study aims to investigate the factors contributing to the livability of public spaces in the Pasar Lama area. This study uses a qualitative method with purposive random sampling, selecting 20 informants from 7 identified public spaces to be interviewed. Primary data includes interviews, observations, mapping, and secondary data from various literature on standards of livable public spaces. The results of this study conclude that sociability and place attachment factors play an important role in making these spaces livable. The high level of social interaction and the existence of supporting facilities at every point in the public space reflect a high level of sociability and encourage public space to continue to be used actively. The strong place attachment felt by residents also creates a sense of responsibility towards the environment where they live.